Taxonomic studies of Cycas debaoensis (Cycadaceae) from China - Xi, Hui-Hui; Zhan, Qing-Qing; Liu, Jian; Feng, Xiu-Yan; Gong, Xun (Phytotaxa, 2024)
Traditionally, species delimitation based on morphological and distributional evidence often leads to over- or underestimation of species diversity. The primary distribution area of Cycas debaoensis includes two habitats, which were initially published as two separate species, i.e., C. debaoensis in the karst habitat, and C. panshuiensis, which was originally published as Cycas gracilis Y.Y. Huang, Y.C. Zhong et Z.F. Lu, in the sand habitat. However, field investigations and population sampling in these two habitats revealed a certain degree of morphological transition and variation among the populations. Subsequent population genetic analysis showed minimal genetic differentiation among the populations in the two habitats, suggesting that they should be merged as a single species. Additionally, the typification of the name C. debaoensis is also discussed.